Land use planning of paddy field using geographic information system and land evaluation in West Lombok, Indonesia - Widiatmaka Widiatmaka; Wiwin Ambarwulan Ambarwulan; Rudi P Tambunan; Yusanto A Nugroho; Suprajaka Suprajaka; Nurwadjedi Nurwadjedi; Paulus B.K. Santoso (Faculty of Geography, Universitas Gadjah Mada, 2014)
Planning analysis to increase rice production either through intensiḀcation of existing paddy Ḁeld area or ex-tensiḀcation in potential land area was conducted in West Lombok Regency, West Nusa Tenggara Province, Indonesia. Existing paddy Ḁeld was delineated using high-resolution data from IKONOS imagery of 2012. Land use and land cover outside existing paddy Ḁeld were interpreted using SPOT-5 imagery of 2012. ἀe Automated Land Evaluation System (ALES) was used for land suitability analysis for paddy. ἀe results are interpreted in terms of the potential of paddy Ḁeld intensiḀcation in existing paddy Ḁeld area and the potential of extensiḀcation in land potentially used for paddy Ḁeld. ἀe result of analysis showed that in West Lombok Regency, there are still possible to do intensiḀcation and extensiḀca-tion of paddy Ḁeld to increase rice production in order to improve regional food security.